Pelatihan Penyusunan Laporan Arus Kas pada BUMDes Bintang Muda Mandiri Desa Sialang Kubang, Kecamatan Perhentian Raja, Kabupaten Kampar - Fitriyeni Oktavia; Sanda Patrisia Komala Sari; Berri Briliant Albar; Ares Albirru Amsal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The cash flow statement provides relevant information regarding cash receipts and payments of a company in one period. The information presented on it assists the company in making decisions on using available cash. It serves as the basis for evaluating the performance of receiving and cash disbursement in a period. Decision errors can result in several circumstances, such as debt accumulation, jammed cash inflows, uncollectible customer receivables, and BUMDes' failure to pay for daily operational needs. BUMDes Bintang Muda Mandiri is one of the best BUMDes from the Deepening Program of Bank BRI Brilian Village, a village incubation program organized by PT Bank Rakyat Indonesia, Tbk. in 2022. BUMDes Bintang Muda Mandiri has also reported profits in the last three years, which reflects the potential for future growth. This community service activity provided training in preparing a Statement of Cash Flow using Excel worksheets prepared by the Andalas University Community Service Team. The method used in this activity was the delivery of material and training. The benefit of this activity was the realization of independent BUMdes human resources who can prepare the cash flow statement and analyze it as a financial report for decision-making.